Overtime work as a form of work exploitation - Kuzminac, Mina (Sociološki pregled, 2021)
In the paper, the author analyzes the normative framework that regulates overtime work at the international and national level, but also the issue of overtime work in practice. The author puts forward the thesis that employers resort to overtime work in order to reduce labour costs, and employees agree to work overtime, even when it is illegal, due to the fear of dismissal, so by such abuse by employers, overtime work becomes a form of work exploitation. The author has conducted the research through a survey and an interview in order to determine the extent to which (illegal) overtime work is present in practice. The results of the research show that unpaid overtime work is widely present and that employees are afraid to stand up against this practice. In conclusion, there is a discrepancy between the normative and the real when it comes to overtime work.
Keywords: working hours; overtime; normative framework; practice; mental health of employees